Supplementation of red palm olein-enriched biscuits improves levels of provitamin A carotenes, iron, and erythropoiesis in vitamin A-deficient primary schoolchildren: a double-blinded randomised controlled trial - Tan, Pei Yee; Radhika, Loganathan; Teng, Kim-Tiu; Syahirah Nadiah, Mohd Johari; Lee, Soo Ching; Selvaduray, Kanga Rani; Romano, Ngui; Yvonne Lim, Ai Lian (Springer Nature Limited, 2024)
Purpose Vitamin A deficiency (VAD) remains a significant contributor to childhood morbidity and mortality in developing countries; therefore, the implementation of sustainable and cost-effective approaches to control VAD is of utmost pertinence. This study aims to investigate the efficacy of red palm olein (RPO)-enriched biscuit supplementation in improving vitamin A, haematological, iron, and inflammatory status among vitamin A-deficient schoolchildren. Methods We conducted a double-blinded, randomised controlled trial involving 651 rural primary schoolchildren (8–12 years) with VAD in Malaysia. The schoolchildren were randomised to receive either RPO-enriched biscuits (experimental group, n = 334) or palm olein-enriched biscuits (control group, n = 317) for 6-month duration. Results Significant improvements in retinol and retinol-binding protein 4 levels were observed in both groups after supplementation (P < 0.001). The improvement in retinol levels were similar across groups among subjects with confirmed VAD (P = 0.40). Among those with marginal VAD, greater improvement in retinol levels was recorded in the control group (P < 0.001) but lacked clinical significance. The levels of α- and β-carotenes, haematological parameters (haemoglobin, packed cell volume, mean corpuscular volume and mean corpuscular haemoglobin) and iron enhanced more significantly in the experimental group (P < 0.05). The significant reduction in the prevalence of microcytic anaemia (− 21.8%) and high inflammation (− 8.1%) was only observed in the experimental group. Conclusion The supplementation of RPO-enriched biscuits enhanced levels of provitamin A carotenes, iron, and erythropoiesis, and exhibited anti-inflammatory effects. Therefore, the incorporation of RPO into National Nutritional Intervention Programs may be a potential measure to improve the health status of vitamin A-deficient children, among various other interventions. Clinical trial registration ClinicalTrials.gov (NCT03256123).